On the Vicarious Humanity of Christ. (29th July 2019) - Crisp, Oliver D.
Abstract: In the recent literature there has been a spate of essays, articles and books discussing the question of whether Christ had a 'fallen' human nature. This article offers a new argument for the conclusion that Christ had a fallen but not sinful human nature that was 'healed' of its fallenness at the moment of assumption by the Word – what we shall call, the vicarious humanity of Christ view. This account concedes to the defender of Christ's 'fallen' humanity that his human nature is generated in a fallen state (and immediately cleansed of fallenness in the act of assumption). And it concedes to the defender of Christ's sinlessness the claim that Christ is without sin from the first moment of incarnation. This represents an important via media in the contemporary debate about this vexed christological topic.